Low crater frequencies and low model ages in lunar maria: Recent endogenic activity or degradation effects?. (17th January 2018) - Valantinas, A.; Kinch, K. M.; Bridžius, A.
Abstract: Recently a number of studies have identified small lunar geologic structures to be <100 Ma in age using standard remote sensing techniques. Here we present new crater size frequency distributions (CSFDs) and model ages using craters D  > 10 m for five small target units: one irregular mare patch (IMP) in Mare Nubium and four regions located on lunar wrinkle ridges in Mare Humorum. For comparison we also date another IMP found in a recent study in Mare Tranquillitatis (Braden et al.2014 ). Absolute model age (AMA) derivation corresponds to 46 ± 5 Ma and 22 ± 1 Ma for Nubium and Sosigenes IMP, respectively. We show that for IMPs and in nearby control mare regions, similar production‐like cumulative log–log SFD slopes of −3 are observed. In contrast, control mare regions in Mare Humorum exhibit shallower equilibrium slopes from −1.83 to −2. Three out of four wrinkle ridges appear to be in equilibrium but with crater lifetimes lower than on the corresponding maria. Low crater frequencies on one wrinkle ridge result in an age of 8.6 ± 1 Ma. This study region contains 80% fresh craters, which suggests that the crater population is still in production indicative of a recent resurfacing event.